Ensuring the value chain as a factor in industrial competitiveness (Journal of Economic Research & Business Administration, 2018)
This article examines the issues related to the assessment of the competitiveness of enterprises, inparticular, the oil refining industry. Also, the article describes the tasks of managing the value chain, thesolution of which will lead to the achievement of the main objective of the enterprise, which will entail anincrease in the investment attractiveness and competitiveness of the enterprise. In the market system ofmanagement, the problem of forming such a value creation chain is being actualized, which, on the onehand, allows an enterprise to increase its own economic efficiency, and on the other, does not burden itwith performing unusual activities and does not reduce the specialization effect. The development of themarket economy actualizes the problem of increasing the competitiveness of Kazakhstani enterprises.When solving this problem, an important task is to establish the reasons preventing the growth of thecompetitiveness of enterprises in a particular industry. Achieving competitiveness, and – more importantly– maintaining competitive positions for a long time, is possible only with such an organizationof production and marketing processes that functions more efficiently than competitors. This article willanalyze the features of the organization of the value chain in a company operating in the oil industry.For the rational formation of the value chain of the product, it is necessary to evaluate its effectiveness inorder to maximize the results of the enterprise’s operations.